Gross motor dysfunction and balance impairments in children and adolescents with Down syndrome: a systematic review - Preyal D. Jain; Akshatha Nayak; Shreekanth D. Karnad; Kaiorisa N. Doctor (The Korean Pediatric Society, 2022)
Background Individuals with Down syndrome present with several impairments such as hypotonia, ligament laxity, decreased muscle strength, insufficient muscular cocontraction, inadequate postural control, and disturbed proprioception. These factors are responsible for the developmental challenges faced by children with Down syndrome. These individuals also present with balance dysfunctions. Purpose This systematic review aims to describe the motor dysfunction and balance impairments in children and adolescents with Down syndrome. Methods We searched the Scopus, ScienceDirect, MEDLINE, Wiley, and EBSCO databases for observational studies evaluating the motor abilities and balance performance in individuals with Down syndrome. The review was registered on PROSPERO. Results A total of 1,096 articles were retrieved; after careful screening and scrutinizing against the inclusion and exclusion criteria, 10 articles were included in the review. Overall, the children and adolescents with Down syndrome showed delays and dysfunction in performing various activities such as sitting, pulling to stand, standing, and walking. They also presented with compensatory mechanisms to maintain their equilibrium in static and dynamic activities. Conclusion The motor development of children with Down syndrome is significantly delayed due to structural differences in the brain. These individuals have inefficient compensatory strategies like increasing step width, increasing frequency of mediolateral center of pressure displacement, decreasing anteroposterior displacement, increasing trunk stiffness, and increasing posterior trunk displacement to maintain equilibrium. Down syndrome presents with interindividual variations; therefore, a thorough evaluation is required before a structured intervention is developed to improve motor and balance dysfunction.